2013
DOI: 10.1152/ajpcell.00230.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms of Tissue Fibrosis. 5. Novel insights into liver fibrosis

Abstract: Liver fibrosis is the common scarring reaction associated with chronic liver injury that results from prolonged parenchymal cell injury and/or inflammation. The fibrogenic response is characterized by progressive accumulation of extracellular matrix components enriched in fibrillar collagens and a failure of matrix turnover. This process is driven by a heterogeneous population of hepatic myofibroblasts, which mainly derive from hepatic stellate cells and portal fibroblasts. Regression of fibrosis can be achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
225
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(237 citation statements)
references
References 102 publications
4
225
1
7
Order By: Relevance
“…Liver myofibroblasts used to test antifibrotic drugs L Aoudjehane et al degradation of ECM. 11,25,26 Our results suggest that at least part of this inter-patient variability in fibrosis progression is dependent on the HLMF themselves; their activation and ECM production (in our case, evaluated from α-SMA and Coll1 transcription) and their proliferation vary between subjects, displaying a regular-Gaussian-distribution for the three parameters. We can therefore advance the hypothesis that subjects who spontaneously display higher activation Liver myofibroblasts used to test antifibrotic drugs L Aoudjehane et al and/or proliferation rates of their HLMF are predisposed to being rapid fibrosers, although our present experiments did not allow us to draw any conclusions, because the HLMF were obtained from patients undergoing surgery for metastases, without fibrosing disease and without significant liver fibrosis (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…Liver myofibroblasts used to test antifibrotic drugs L Aoudjehane et al degradation of ECM. 11,25,26 Our results suggest that at least part of this inter-patient variability in fibrosis progression is dependent on the HLMF themselves; their activation and ECM production (in our case, evaluated from α-SMA and Coll1 transcription) and their proliferation vary between subjects, displaying a regular-Gaussian-distribution for the three parameters. We can therefore advance the hypothesis that subjects who spontaneously display higher activation Liver myofibroblasts used to test antifibrotic drugs L Aoudjehane et al and/or proliferation rates of their HLMF are predisposed to being rapid fibrosers, although our present experiments did not allow us to draw any conclusions, because the HLMF were obtained from patients undergoing surgery for metastases, without fibrosing disease and without significant liver fibrosis (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…The progression of liver fibrosis is promoted by oxidative stress [12,13], although this is likely to be just one of multiple processes involved. In the present study, oxidative stress in the liver of octn1 -/-was much greater than that in wild-type mice at 1 and 2 weeks after treatment with DMN (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hepatic stellate cells (HSCs) are activated by oxidative stress to collagen-producing myofibroblasts, which promote liver fibrosis by producing ECM [12,13]. Oxidative stress may also injure parenchymal cells, leading to further 6 progression of liver injury.…”
Section: Ergo Is Minimally Taken Up Into Liver Parenchymal Cells Butmentioning
confidence: 99%
See 1 more Smart Citation
“…However LI-MAIT cells could potentially aggravate liver pathologies. LI-MAIT cells can produce IL-17, which plays a major role in the pathogenesis of several chronic liver disease, of alcoholic, metabolic, viral or autoimmune origin, and contribute to the progression of liver fibrosis [17]. Using a mouse model, Harley et al have demonstrated the pathogenic role of IL-17 in the progression of non-alcoholic fatty liver disease (NAFLD) since IL-17 deficient mice were protected against NAFLD [18].…”
mentioning
confidence: 99%